PHYSICO-CHEMICAL FEATURES OF WATERS AND BIOCOENOSIS OF A MEROMICTIC RESERVOIR IN THE YEARS 1981-1998 IN THE LEKNICA REGION (WESTERN POLAND) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The research concerned the biggest, the deepest and the youngest (25 years old) acidotrophic reservoir located 4 km south-east from Lqknica. It was created as a result of brown-coal mining and opencast method. The present pyrite was the cause of significant acidifying and salinity of waters. 17 years of physico-chemical examinations of waters showed a progressive difference between mixo- and monimolimnion that is increase or decrease of such indicators as pH, redox potential, total iron, sulphate and others. First symptoms of ageing o f the reservoir were visible. Biological examinations showed pancity of plant and animal species living in this reservoir and a very slow development ofbiocoenosis. The research concerned the biggest, the deepest and the youngest (25 years old) acidotrophic reservoir located 4 km south-east from Lqknica. It was created as a result of brown-coal mining and opencast method. The present pyrite was the cause for significant acidifying and salinity of waters. 17 years of physico-chemical examinations of waters showed a progressive difference between mixo- and monimolimnion that is increase or decrease o f such indicators as pH, redox potential, total iron, sulphate and others. First symptoms of ageing o f the reservoir were visible. Biological examinations showed pancity of plant and animal species living in this reservoir and a very slow development of biocoenosis.